Simple models of the cardiovascular system for educational and research purposes - Kulhánek, Tomáš; Tribula, Martin; Kofránek, Jiří; Mateják, Marek (Mefanet journal, 2014)
Modeling the cardiovascular system as an analogy of an electrical circuit composed of resistors, capacitors and inductors is introduced in many research papers. This contribution uses an object oriented and acausal approach, which was recently introduced by several other authors, for educational and research purpose. Examples of several hydraulic systems and whole system modeling hemodynamics of a pulsatile cardiovascular system are presented in Modelica language using Physiolibrary.
Keywords: modely kardiovaskulární; Cardiovascular Physiological Phenomena; studenti lékařství; Physiology; lidé; fyziologie; Models, Cardiovascular; Students, Medical; kardiovaskulární fyziologické jevy; Humans